LITERATUR REVIEW : PENGEMBANGAN MEDIA KAHOOT SEBAGAI MEDIA PEMBELAJARAN SISWA - Maya Febriani Chandra; Irfandi Irfandi; Nofri Yuhelman (Pimpinan Cabang Muhammadiyah Kramat Jati, 2023)
Education is one industry that benefits from the rapid advancement of technology today. Teachers use technology as a learning tool to communicate with their students; One such tool is Kahoot. Anyone wishing to study or teach using modern techniques can use this program with great success. The purpose of this research is to see how the Kahoot learning application is developed. Methods This research method is a literature review. A sample of 10 research and development articles on Kahoot learning media was used in this literature review. Three articles use the 4D model, three articles use the ADDIE model, and four articles use the ADDIE model out of 10 journal articles that review the making of Kahoot learning media. There are three articles using the 4D model, three articles using the ADDIE model, four articles using the Borg&Gall model, and one article using the Borg&Gall model out of ten journal articles that discuss the use of media in classroom learning. From the 10 expert validation articles, valid results were obtained on 86.74% material and 87.54% media. The survey respondents' responses also showed very positive results with an accuracy rate of 89.4%. Therefore, the development of the Kahoot application will provide a positive learning effect, making learning itself more enjoyable.